Hypoxia-inducible protein 2 Hig2/Hilpda mediates neutral lipid accumulation in macrophages and contributes to atherosclerosis in apolipoprotein E-deficient mice - Maier, Anja; Wu, Hao; Cordasic, Nada; Oefner, Peter; Dietel, Barbara; Thiele, Christoph; Weidemann, Alexander; Eckardt, Kai-Uwe; Warnecke, Christina (The FASEB Journal, 2017)
Recently we identified hypoxia-inducible protein 2 (HIG2)/hypoxia-inducible lipid droplet associated (HILPDA) as lipid droplet (LD) protein. Because HILPDA is highly expressed in atherosclerotic plaques, we examined its regulation and function in murine macrophages, compared it to the LD adipose differentiation-related protein (Adrp)/perilipin 2 (Plin2), and investigated its effects on atherogenesis in apolipoprotein E-deficient (ApoE(-/-)) mice. Tie2-Cre-driven Hilpda knockout (cKO) did not affect viability, proliferation, and ATP levels in macrophages. Hilpda proved to be a target of hypoxia-inducible factor 1 (Hif-1) and peroxisome proliferator-activated receptors. In contrast, Adrp/Plin2 was not induced by Hif-1. Hilpda localized to the endoplasmic reticulum-LD interface, the site of LD formation. Hypoxic lipid accumulation and storage of oxidized LDL, cholesteryl esters and triglycerides were abolished in Hilpda cKO macrophages, independent of the glycolytic switch, fatty acid or lipoprotein uptake. Hilpda depletion reduced resistance against lipid overload and increased production of reactive oxygen species after reoxygenation. LPS-stimulated prostaglandin-E2 production was dysregulated in macrophages, demonstrating the substrate buffer and reservoir function of LDs for eicosanoid production. In ApoE(-/-) Hilpda cKO mice, total aortic plaque area, plaque macrophages and vascular Vegf expression were reduced. Thus, macrophage Hilpda is crucial to foam-cell formation and lipid deposition, and to controlled prostaglandin-E2 production. By these means Hilpda promotes lesion formation and progression of atherosclerosis.-Maier, A., Wu, H., Cordasic, N., Oefner, P., Dietel, B., Thiele, C., Weidemann, A., Eckardt, K.-U., Warnecke, C. Hypoxia-inducible protein 2 Hig2/Hilpda mediates neutral lipid accumulation in macrophages and contributes to atherosclerosis in apolipoprotein E-deficient mice.
EVALuna2:4018